Examination of Orbital Tissues in Murine Models of Graves’ Disease Reveals Expression of UCP-1 and the TSHR in Retrobulbar Adipose Tissues - Johnson, K.T. M.; Wiesweg, B.; Schott, M.; Ehlers, M.; Müller, M.; Minich, W. B.; Nagayama, Y.; Gulbins, E.; Eckstein, A. K.; Berchner-Pfannschmidt, U. (Hormone and Metabolic Research, 2013)
Over the past decade a number of murine models of Graves’ disease (GD) have been described. The full symptom complex, including typical orbital changes, however, could not yet be induced. In this report, we examined the influence of modified immunization protocols on orbital pathology. C57BL/6 and BALB/c mice were immunized against the human TSH receptor (TSHR), using either a TSHR encoding plasmid or a TSHR A-subunit adenovirus. Prior to immunization with the TSHR plasmid, regulatory T cells were depleted in one group of each strain. TSHR-stimulating antibodies (TSAbs) were evaluated and orbits were stained immunohistochemically for F4/80, uncoupling protein-1 (UCP-1) and the TSHR. We found that after depletion of regulatory T cells, incidence of TSAb was increased in TSHR plasmid immunized C57BL/6 mice. Examination of early immunized mice showed no antibody production. However, a TSHR epitope-specific cellular immune response could be detected by tetramer-analyses. Adenoviral immunization lead to TSAb production in all but one animal. Analysis of F4/80 positive cells in retrobulbar fat revealed no significant macrophage infiltration in the orbits of immunized mice. Immunohistochemical staining shows co-localization of F4/80 positive cells, UCP-1 and the TSHR in retrobulbar fat. Though targets for TSHR autoimmunity could clearly be shown, immunization methods were not efficient enough to cause clear signs of orbital inflammation.
Keywords: Graves’ orbitopathy; animal model; brown adipose tissue; macrophages